2015
DOI: 10.1098/rsbl.2015.0506
|View full text |Cite
|
Sign up to set email alerts
|

Explaining large-scale patterns of vertebrate diversity

Abstract: The major clades of vertebrates differ dramatically in their current species richness, from 2 to more than 32 000 species each, but the causes of this variation remain poorly understood. For example, a previous study noted that vertebrate clades differ in their diversification rates, but did not explain why they differ. Using a time-calibrated phylogeny and phylogenetic comparative methods, I show that most variation in diversification rates among 12 major vertebrate clades has a simple ecological explanation:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 16 publications
3
71
0
Order By: Relevance
“…For example, recent studies have found significant relationships between increased rates of species diversification and occurrence in tropical regions (e.g., Rolland et al. 2014), occurrence on land instead of in water or in marine environments (e.g., Wiens 2015a,b), the presence of defense mutualisms in plants (Weber and Agrawal 2014), and the presence of herbivory in insects (e.g., Wiens et al. 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies have found significant relationships between increased rates of species diversification and occurrence in tropical regions (e.g., Rolland et al. 2014), occurrence on land instead of in water or in marine environments (e.g., Wiens 2015a,b), the presence of defense mutualisms in plants (Weber and Agrawal 2014), and the presence of herbivory in insects (e.g., Wiens et al. 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In general, differences in species richness can be associated with heterogeneity in the rates of species diversification, but the drivers of such rate heterogeneity remain poorly explored for many groups of species. As exemplified by well-known radiations [7][8][9][10][11], high species diversity is often mirrored by high levels of eco-morphological variation, suggesting that species diversification is linked to evolutionary change [12 -14]. However, little is known about the ubiquity of the coupling between ecological divergence, phenotypic evolution and species diversification.…”
Section: Introductionmentioning
confidence: 99%
“…The ages of the Vertebrata origin estimated by Hedges and Kumar (2009) are older than those estimated by Wiens (2015). These time trees differ in the crown age of Vertebrata by about 100 My.…”
Section: Timing Of Diversificationmentioning
confidence: 72%
“…A complete figure including all species analysed in this study is found in Supplementary Figure S1. (B) A timetree representing temporal patterns of diversification in major lineages of vertebrates. Topology and divergence dates are consensus estimates derived from Kumar (2009) andWiens (2015). Confidence intervals among vertebrate clades are found in each branch following estimates from Blair and Hedges (2005) and Kumar and Hedges (1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation